Comparison of Utility-First CSS Framework - Nandan, S.; Usha, Sree R.; Priyanka, Mohan (INTI International University, 2024)
Utility-first CSS frameworks have revolutionized web development by offering predefined utility classes that streamline the design process and reduce the need for custom CSS. However, selecting the right framework can be challenging due to the variety of available options. This paper addresses the problem of choosing between two of the leading utility-first CSS frameworks Tailwind CSS and Tachyons by providing a comparative analysis based on key factors such as size, load speed, flexibility, ease of use, and community support. The objective of this research is to identify the strengths and weaknesses of both frameworks, helping developers make informed decisions based on project needs. Our methodology involved testing load speeds using Locust for performance analysis, reviewing community support through GitHub repositories and forums, and assessing the flexibility and ease of use through practical development tasks. The results revealed that while both frameworks are robust, Tachyons excels in performance and simplicity due to its smaller size, whereas Tailwind CSS offers greater customization and flexibility, making it more suitable for complex projects. The novelty of this research lies in its direct comparison of utility-first frameworks, highlighting how developer preferences and project requirements play a crucial role in framework selection. In summary, this study provides valuable insights for developers looking to optimize web development workflows by selecting the most appropriate CSS framework based on specific project goals.